MODERN METHODS OF ENSURING MOBILE APPLICATION SECURITY (Ustozlar uchun, 2026)
This article examines modern methods of ensuring mobile application security, security threats arising during data exchange through mobile devices, and mechanisms for preventing cyber risks. The study analyzes major cybersecurity threats in mobile applications, including malware, phishing attacks, data leakage, authentication vulnerabilities, and network-related security issues. In addition, the article discusses the effectiveness of advanced encryption algorithms, multi-factor authentication systems, biometric protection technologies, and artificial intelligence in enhancing mobile application security. The findings demonstrate that implementing modern cybersecurity approaches plays a significant role in improving data protection, maintaining user privacy, and ensuring secure digital communication in mobile platforms.